POWER ENGINEERING: NUCLEAR POWER PLANTS AND RENEWABLE ENERGY SOURCES - Adamtsevich, Aleksey Adamtsevich; Solovyev, Alexander; Pustovgar, Andrey; Shilova, Liubov; Degtyarev, Kirill; Solovyev, Dmitry (Journal of Applied Engineering Science, 2017)
The article considers a comparative dynamics of power engineering development based on the use of nuclear energy and renewable energy sources science 1960s. The authors evaluate the parameters of environmental and economic efficiency, risks and prospects of power engineering development based on various types of energy carriers. It is shown that the reduction of the share of nuclear power engineering in the world energy balance cannot be compensated due to renewable energy sources, and it would cause the increase in the use of fossil fuels. The authors come to the conclusion about the necessity of a parallel development of both the renewable energy sources and the nuclear power engineering
Keywords: Environment; Nuclear energy; Renewable energy sources; Power engineering politics